2023
DOI: 10.1055/a-2060-0935
|View full text |Cite
|
Sign up to set email alerts
|

Aktualisierte S3-Leitlinie Colitis ulcerosa (Version 6.1) – Februar 2023 – AWMF-Registriernummer: 021-009

T. Kucharzik,
A. Dignass,
R. Atreya
et al.

Abstract: Ambulant und stationär, hausärztlich, pädiatrisch, internistisch, chirurgisch und gastroenterologisch. Anwenderzielgruppe/Adressaten Die Leitlinie richtet sich an alle an der Diagnostik und Therapie beteiligten Berufsgruppen Internist*innen, Kinder-und Jugendmediziner*innen, Chirurg*innen, Proktolog*innen, Gastroenterolog*innen, Patholog*innen, Ernährungsmediziner*innen, Fachassistenz CED, Patientenvertreter*innen sowie Betroffene, Angehörige und dient zur Information für Leistungserbringer (Krankenkassen, Ren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 833 publications
(1,203 reference statements)
0
1
0
Order By: Relevance
“…Probiotics, live bacteria believed to promote health, have been recognized for their beneficial effects for many decades in different indications. The use of the probiotic Escherichia coli (E. coli) Nissle 1917 is recommended in guidelines for patients with ulcerative colitis ( 78 ). A pilot study by an Italian group demonstrated that the intake of various probiotics over 8 weeks led to a modification of well-being status, as well as inflammatory and oxidative indexes in CFS/ME patients, resulting in a reduction of inflammatory parameters after probiotic intake ( 13 )( Table 1 ).…”
Section: Modulation Of the Gastrointestinal Microbiome As Rational Th...mentioning
confidence: 99%
“…Probiotics, live bacteria believed to promote health, have been recognized for their beneficial effects for many decades in different indications. The use of the probiotic Escherichia coli (E. coli) Nissle 1917 is recommended in guidelines for patients with ulcerative colitis ( 78 ). A pilot study by an Italian group demonstrated that the intake of various probiotics over 8 weeks led to a modification of well-being status, as well as inflammatory and oxidative indexes in CFS/ME patients, resulting in a reduction of inflammatory parameters after probiotic intake ( 13 )( Table 1 ).…”
Section: Modulation Of the Gastrointestinal Microbiome As Rational Th...mentioning
confidence: 99%